MANAJEMEN WEB UNTUK MENDUKUNG APLIKASI INFORMASI PETA DIGITAL PADA SMARTPHONE BERBASIS ANDROID - Nugroho, Elihu Setyo (Compiler, 2012)
The society with massive schedule in the fully modern life, gives effect of limitation to the society in doing many activities. For example, while taking a trip in a city without knowing the area might cause many troubles. Using location searching in a city using GPS technology which connected to the android smartphone tools, will make it easier and  saving cost, time and energy.             The method of this research for the mapping is using google map  facility. In this application, the data like mesjid, church, market, hotel, restaurant and hospital data is saved in server web which make possible for the user to add new data to the application with verification performed by the administrator.             Smartphone tools which have GPS facility can be used to acknowledge important spot location in a city and the user location at the sam time. This kind of application can be functioned if this smartphone tools with facility GPS has connection with the internet.